On following pages: 13. Harp Seal (Pagophilus groenlandicus); 14. Harbor Seal (Phoca vitulina); 15. Spotted Seal (Phoca largha); 16. Caspian Seal (Pusa caspica); 17. Baikal Seal (Pusa sibirica); 18. Ringed Seal (Pusa hispida). in Phocidae - Russell A. Mittermeier; Don E. Wilson (PLOS ONE, 2014)
On following pages: 13. Harp Seal (Pagophilus groenlandicus); 14. Harbor Seal (Phoca vitulina); 15. Spotted Seal (Phoca largha); 16. Caspian Seal (Pusa caspica); 17. Baikal Seal (Pusa sibirica); 18. Ringed Seal (Pusa hispida). Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 179, DOI: 10.5281/zenodo.6607185